Systemic long‐term inactivation of hypoxia‐inducible factor prolyl 4‐hydroxylase 2 ameliorates aging‐induced changes in mice without affecting their life span. Issue 4 (25th February 2020) - Laitakari, Anna; Huttunen, Riikka; Kuvaja, Paula; Hannuksela, Pauliina; Szabo, Zoltan; Heikkilä, Minna; Kerkelä, Risto; Myllyharju, Johanna; Dimova, Elitsa Y.; Serpi, Raisa; Koivunen, Peppi
Abstract: Hypoxia inactivates hypoxia‐inducible factor (HIF) prolyl 4‐hydroxylases (HIF‐P4Hs), which stabilize HIF and upregulate genes to restore tissue oxygenation. HIF‐P4Hs can also be inhibited by small molecules studied in clinical trials for renal anemia. Knowledge of systemic long‐term inactivation of HIF‐P4Hs is limited but crucial, since HIF overexpression is associated with cancers. We aimed to determine the effects of systemic genetic inhibition of the most abundant isoenzyme HIF prolyl 4‐hydroxylase‐2 (HIF‐P4H‐2)/PHD2/EglN1 on life span and tissue homeostasis in aged mice. Our data showed no difference between wild‐type and HIF‐P4H‐2‐deficient mice in the average age reached. There were several differences, however, in the primary causes of death and comorbidities, the HIF‐P4H‐2‐deficient mice having less inflammation, liver diseases, including cancer, and myocardial infarctions, and not developing anemia. No increased cancer incidence was observed due to HIF‐P4H‐2‐deficiency. These data suggest that chronic inactivation of HIF‐P4H‐2 is not harmful but rather improves the quality of life in senescence.